RETRACTED: The Construction of Ecosystem and Collaboration Platform for Enterprise Open Innovation - Wang, Maoxiang; Zhang, Ruili; Abdulwase, Rasheed; Yan, Shuangsheng; Muhammad, Mohsin (Frontiers in Psychology, 2022)
In the era of knowledge economy which is fulfilled with fierce competition, traditional closed innovation can no longer meet the market demand, and the enterprise needs to implement open innovation involving external resources. The concept of open innovation emphasizes both the use of internal and external resources in the process of enterprise innovation and the use of internal and external markets to promote the commercialization of innovation achievements. With the rapid development of Internet technology, enterprises must build an open innovation ecosystem of benefits-sharing, pay attention to identifying, connecting and utilizing external innovation resources, and be committed to creating an open innovation ecosystem without organizational boundaries. Enterprises should pay attention to coordinating the relationship among the innovation ecosystem members, eliminating heterogeneous barriers between enterprises and their partners, and enhancing the cooperative innovation ability with external organizations. It is also necessary to build an innovation collaborative platform, which is convenient for the release and acquisition of innovation information, the collection of customer needs and related ideas, and the full use of external resources for innovation. In particular, it is necessary to guide users and related resources to the innovation platform, realize the maximum effect of resource aggregation and promote customer demand-oriented new product development. Through building an open innovation ecosystem and a collaboration platform, it is helpful for enterprises to seek all kinds of technical and resource support, enhance the ability of independent innovation, promote the emergence of many innovative achievements, and realize value co-creation and win-win cooperation with partners.